RISK FOR SWITCH FROM UNIPOLAR TO BIPOLAR DISORDER IN YOUTH WITH ADHD: A LONG TERM PROSPECTIVE CONTROLLED STUDY - Biederman, Joseph (2009)
BACKGROUND: To investigate whether ADHD is a risk factor for switches from unipolar to bipolar disorder over time. METHODS: Data from two large controlled longitudinal family studies of boys and girls with and without ADHD and their siblings were used. Subjects (n=168) were followed prospectively and blindly over an average follow up period of 7 years. Comparisons were made between youth with unipolar major depression who did and did not switch to full or subthreshold BP-I disorder at the follow-up assessment. Subjects were assessed at baseline and follow-up on multiple domains of functioning. Positive family history of parental psychiatric disorders was also compared between groups. RESULTS: ADHD was associated with a significantly higher risk for switches from unipolar to bipolar disorder (28% vs 6%; z=2.80, p=0.005). In subjects with ADHD, switches from unipolar to bipolar disorder were predicted by baseline comorbid conduct disorder, school behavior problems, and a positive family history of parental mood disorder. LIMITATIONS: Psychosis was an exclusionary criterion in the original ascertainment of the studies of ADHD probands, so we were unable to test this as a predictor of switching to BPD. CONCLUSIONS: ADHD is a risk factor for switches from unipolar to bipolar disorder, and switches could be predicted by the presence of baseline conduct disorder, school behavior problems, and a positive family history of a mood disorder in a parent. These characteristics can aid clinicians in their treatment of youth with MDD.